2021
DOI: 10.3233/jvr-201130
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analyses of employment services for individuals with intellectual and developmental disabilities: A scoping review

Abstract: BACKGROUND: Understanding the cost-benefit of vocational rehabilitation services is critical to improve competitive integrated employment outcomes for individuals with intellectual and developmental disabilities (IDD). OBJECTIVE: The purpose of this scoping review was to analyze and synthesize micro and macroeconomic analyses of various types of vocational services which promote the employment outcomes of individuals with IDD. METHODS: This scoping review searched peer-reviewed and grey literature sources publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…As individuals with ASD may possess varying levels of social competencies, interventions that enhance social skills can be particularly effective for job‐related activities such as interviewing and interpersonal interactions with other employees (Grob et al, 2019 ). Although many individuals with autism are currently served in segregated prevocational settings, previous research has indicated that individuals with previous experience in these segregated settings are actually less likely to eventually gain competitive integrated employment (Taylor et al, 2021 ). In addition to job development services, another set of interventions often targets work‐related skills such as specific job training tasks that may help individuals with ASD maintain their employment through on‐the‐job training and long‐term support (Schall et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…As individuals with ASD may possess varying levels of social competencies, interventions that enhance social skills can be particularly effective for job‐related activities such as interviewing and interpersonal interactions with other employees (Grob et al, 2019 ). Although many individuals with autism are currently served in segregated prevocational settings, previous research has indicated that individuals with previous experience in these segregated settings are actually less likely to eventually gain competitive integrated employment (Taylor et al, 2021 ). In addition to job development services, another set of interventions often targets work‐related skills such as specific job training tasks that may help individuals with ASD maintain their employment through on‐the‐job training and long‐term support (Schall et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, there is a direct reduction of unemployment risk following the intervention. This reduced unemployment risk may reflect that the 3-year program employs participants directly in the community (Taylor et al, 2021) and provides support across multiple domains of the autistic person’s functioning (e.g. environmental, individual) while taking a strengths-based perspective (Scott et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In operationalising CIE as a public service outcome and the goal of policy, conceptualization has primarily been as an outcome in-and-of-itself. However, research has also indicated that CIE may in turn provide other advantages and opportunities for individuals with disabilities; beyond serving as an outcome in and of itself, meaningful employment may provide economic opportunity (e.g., Taylor et al, 2021), better quality of life (e.g., Beyer et al, 2010;Dean et al, 2018;Iwanaga et al, 2021), and perhaps even better health outcomes (e.g., Inge et al, 2009;Robertson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In operationalising CIE as a public service outcome and the goal of policy, conceptualization has primarily been as an outcome in‐and‐of‐itself. However, research has also indicated that CIE may in turn provide other advantages and opportunities for individuals with disabilities; beyond serving as an outcome in and of itself, meaningful employment may provide economic opportunity (e.g., Taylor et al, 2021), better quality of life (e.g., Beyer et al, 2010; Dean et al, 2018; Iwanaga et al, 2021), and perhaps even better health outcomes (e.g., Inge et al, 2009; Robertson et al, 2019). These benefits of employment are not limited to individuals with intellectual and developmental disabilities; research examining the global population (with and without disabilities) has found substantial links between employment and happiness, quality‐of‐life, and other non‐monetary benefits (De Neve & Ward, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation